Effects of varying amounts of Na on Pd/TiO2 for the direct synthesis of H2O2: Identification of the Pd dispersion and catalytic activity enhancement by changing the surface electronic states - Cho, Young-Hoon; Han, Geun-Ho; Han, Sang Soo; Seo, Myung-gi; Lee, Kwan-Young (ELSEVIER, 2020)
Alkali elements have been applied as promoters of noble metals (e.g., Pd or Pt) to enhance their catalytic activities by changing the surface electronic states of the noble metals. In particular, the role of alkali elements is to improve the dispersion properties of the active metal. In this study, various amounts of the alkali element sodium (Na) were used as a promoter for a Pd/TiO2 catalyst. Importantly, the catalysts were synthesized to improve the selectivity and production rate of the direct synthesis of hydrogen peroxide (DSHP) by increasing the Pd dispersion and surface area by changing the surface electronic properties. After the addition of Na onto Pd/TiO2, the H2O2 production rates were generally higher than those for pure Pd/TiO2 due to the synergistic effects between the Pd and Na on the TiO2 support. Particularly, among the tested catalysts, the 0.5 wt.% Na-promoted Pd/TiO2 (PdNa(0.6)/TiO2) catalyst exhibited the highest H-2 conversion rate (22 %) in the iso-Pd weight and the highest H2O2 selectivity (95.4 %) and production rate (785.9 mmol/g(pa)h) for the iso-H-2 conversion test. Na provides electrons to the Pd species, leading to a change in the Pd dispersion. Furthermore, the surface electronic state of Pd changed with increasing amounts of Na, and thus, heavily influenced the H2O2 selectivity. Ultimately, PdNa(0.6)/TiO2 achieved the best selectivity as a H2O2 producing catalyst in this study.
Keywords: HYDROGEN-PEROXIDE; SELECTIVE OXIDATION; PALLADIUM CATALYSTS; H-2 ANDO(2); FORMALDEHYDE; OXYGEN; DECOMPOSITION; HYDRIDE; SITES; ATOMS